PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MICROSOFT POWERPOINT TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI SEGITIGA KELAS VII MTS RAUDLATUT THALIBIN - Tri Astindari; Irma Noervadila; Nur Hasanah (STKIP PGRI Situbondo, 2024)
In this study, the goal to be achieved is to determine whether there is an influence of the use of Microsoft PowerPoint learning media on students' mathematics learning outcomes in class VII MTs Raudlatut Thalibin triangle material. After analyzing the data and testing the hypothesis, the value of the correlation coefficient level between the use of Microsoft PowerPoint learning media (X) and learning outcomes (Y) is 0.678. In testing the hypothesis the result is that there is a high influence between the use of Microsoft PowerPoint learning media and student learning outcomes. Then prove the working hypothesis (Ha) using the F test, Ha will be proven if Fcount is greater than Ftable with a significant level of 5%. The Fcount is 32.240 while the F-table is 4.098 at N = 40, meaning that Fcount is greater than Ftable so that it is said that there is a significant influence between the use of Microsoft PowerPoint learning media on learning outcomes. The effective contribution or influence of the use of Microsoft PowerPoint learning media on learning outcomes is 45.91% in class VII students of MTs Raudlatut Thalibin